Dampak Kualitas Pelayanan dan Harga terhadap Kepuasan Pelanggan pada Toko Bahan Bangunan Wisma Jaya Kediri - Ardhana, Ahmad Brian Farisya; Saptaria, Lina (Jurnal Samudra Ekonomi dan Bisnis, 2025)
The study aims to investigate the effect of service quality and price on customer satisfaction at the Wisma Jaya building materials store in Kunjang District, either partially or simultaneously. This study uses a descriptive quantitative approach. The population is all store customers from 2021-2024. The sampling technique used purposive sampling of 154 customers. A questionnaire was used to collect data, then instrument testing and data analysis were carried out using SPSS software version 26. The results show that service quality and price, both partially and simultaneously, have a positive and significant effect on customer satisfaction. The implications of the results of this study emphasize the importance of store managers to focus on improving service quality and setting competitive product prices as the main strategy in increasing customer satisfaction.